Effect of SynagisⓇ (palivizumab) prophylaxis on readmission due to respiratory syncytial virus in very low birth weight infants - Soo Kyoung Park; Yu Jin Jung; Hye Soo Yoo; So Yoon Ahn; Hyun Joo Seo; Seo Heui Choi; Myo Jing Kim; Ga Won Jeon; Soo Hyun Koo; Kyung-Hoon Lee; Yun Sil Chang; Won Soon Park (Korean Pediatric Society, 2010)
Purpose : The aim of this study was to determine the efficacy of SynagisⓇ (palivizumab) in reducing the respiratory syncytial virus (RSV) readmission rate in very low birth weight infants (VLBWI ) and the subgroup that showed the most effective vaccination. Methods : We enrolled 350 VLBWI who had been discharged alive from the neonatal intensive care unit of Samsung Medical Center from January 2005 to December 2007 and were followed up for at least one year. A retrospective study based on medical records was performed for a period of one year after discharge. RSV readmission rate was investigated according to BPD (bronchopulmonary dysplasia, requiring oxygen at postnatal day 28) and SynagisⓇ prophylaxis. We categorized the subgroups by the severity of BPD gestational age, and birth weight and compared the RSV readmission rates between subgroups. Results : Eleven VLBWI were readmitted. SynagisⓇ prophylaxis resulted in a 86% reduction in the rate of readmission due to RSV infection (prophylaxis group, 0.7% and no prophylaxis group, 5.0%; P=0.02). Readmission rate in BPD patients was also reduced in the prophylaxis group (0.7% in the prophylaxis group vs. 5.2% in the no prophylaxis group, P= 0.03). The readmission rate in patients without BPD was reduced in the prophylaxis group (0% in the prophylaxis group vs. 4.9% in the no prophylaxis group, P=1.00), but this was not statistically significant. Conclusion : SynagisⓇ prophylaxis was effective at reducing RSV readmission in VLBWI. Its efficacy was verified irrespective of BPD, gestational age, or birth weight.